2019
DOI: 10.1530/ec-18-0456
|View full text |Cite
|
Sign up to set email alerts
|

Update on the impact of type 2 diabetes mellitus on bone metabolism and material properties

Abstract: The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide, especially as a result of our aging society, high caloric intake and sedentary lifestyle. Besides the well-known complications of T2DM on the cardiovascular system, the eyes, kidneys and nerves, bone strength is also impaired in diabetic patients. Patients with T2DM have a 40–70% increased risk for fractures, despite having a normal to increased bone mineral density, suggesting that other factors besides bone quantity must account for i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 182 publications
(228 reference statements)
3
82
0
15
Order By: Relevance
“…33 Type 2 diabetes mellitus adversely effects bone metabolism and strength and increases the risk of fracture in affected individuals. 34…”
Section: Bone Fracturesmentioning
confidence: 99%
“…33 Type 2 diabetes mellitus adversely effects bone metabolism and strength and increases the risk of fracture in affected individuals. 34…”
Section: Bone Fracturesmentioning
confidence: 99%
“…Accordingly, the association between diabetes mellitus and bone health has long been a matter of debate. However, several studies have shown that diabetic bone is characterized by abnormal alterations in bone metabolism, decreased bone mineral content and density, increased fracture rate, and delayed fracture healing [13][14][15]. Furthermore, in diabetes mellitus, bone turnover is reduced or disrupted in parallel with increased risk of bone fractures, in which bone formation declines with reduced mineralization and bone cell number [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…43 The underlying mechanism of increased bone fragility in individuals with T2DM may involve hyperglycemia, insulinopenia, reduced level of insulin-like growth factor 1, adipokines, and cytokines affecting osteocyte, accumulation of advanced glycation end products facilitating cross-link with collagen, and late diabetic complications, such as DR and diabetic kidney disease (DKD), which may increase the risk of falling. 33,44 Furthermore, a number of observational studies have suggested the association between MVCs and an increased incidence of fracture. A study indicating that patients with T2DM with MVCs characterized by deteriorations in cortical bone 22 found that biochemical bone markers, including OC, P1NP, and β-CTX, were reduced in the patients with MVCs, which is mostly consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…BTMs are suggested to be useful indicators in monitoring treatment and diagnosing for secondary causes of osteoporosis 25 as well as independent predictors for osteoporosis [26][27][28] and fracture risk. 29,30 Although there are a number of studies reporting the relationships between bone metabolism, indicated by BTMs, and T2DM, [31][32][33] few studies have focused on the interrelationships between bone biochemical markers and DR, 34,35 in particular, and its severity. Additionally, these researches revealed conflicting and inconclusive results.…”
Section: Introductionmentioning
confidence: 99%